Trabajo Social en la calle con personas sin hogar con enfermedad mental - NAVARRO FERNÁNDEZ, Marta; DARDER MAYER, María José (Cuadernos de Trabajo Social, 2010)
This article shows how social work on the street is carried out as part of the Psychiatric Attention Program for Homeless People with Mental Illness. The client’s recovery is based, firstly, on encouraging their participation in the decision-making process, secondly, on ensuring that they take responsibility for their own recovery process, and finally, on fostering their capacities.
Keywords: Social Work on the street; Mental health; Networking and coordination; Ongoing support and follow up; Process networking; Coordination and other strategies